Terminal interruption of relux source technique in the treatment of active venous ulcers - López Lugo, Omar Federico; Salinas Domínguez, Rogelio; Tamez del Bosque, Juan Antonio; Muñoz Maldonado, Gerardo Enrique (UANL. Facultad de Medicina, 2014)
Introduction: The treatment for venous ulcers in most cases is unsatisfactory, with recurrences and poor healing. Objective: to evaluate adjuvant therapy in the treatment of active venous ulcers. Methods: We analyzed 20 patients with active venous ulcers attending the general Surgery outpatient clinic at the “Dr. José eleuterio gonzález” University Hospital from October 2012 to January 2013. they were randomly divided into 2 groups: group A (11 patients) underwent compression therapy and group B (9 patients) underwent compression therapy plus removal of the vein that gives terminal relux to the ulcer, guided by ultrasound (microphlebectomy). Patients were evaluated weekly (8 weeks). At each assessment, photographs and lesion measurements were taken and pain was evaluated using the visual analog scale. Results: No significant differences were found between the study groups in terms of age, weight, height, body mass index (BMi), ankle-brachial index, and baseline measurement of the ulcer (p>0.05). Group B showed a greater reduction in ulcer size and a statistically signiicant lower score on the visual analog pain scale (p<0.05) from the second and third week of treatment, respectively. Conclusions: the results obtained in patients with surgical procedure (group B) are consistent with the reported eficacy of chronic venous ulcer treatment with saphenectomy (conventional surgery), the difference is that in this study we used a minimally invasive procedure (microphlebectomy).